Comparison of oxygen uptake during and after the execution of resistance exercises and exercises performed on ergometers, matched for intensity - Vilaça-Alves, José (J Hum Kinet, 2016)
The aim of this study was to compare the values of oxygen uptake (VO2) during and after strength training exercises (STe) and ergometer exercises (Ee), matched for intensity and exercise time. Eight men (24 ± 2.33 years) performed upper and lower body cycling Ee at the individual’s ventilatory threshold (VE/VCO2). The STe session included half squats and the bench press which were performed with a load at the individual blood lactate concentration of 4 mmol/l. Both sessions lasted 30 minutes, alternating 50 seconds of effort with a 10 second transition time between upper and lower body work. The averaged overall VO2 between sessions was significantly higher for Ee (24.96 ± 3.6 ml·kg·min(-1)) compared to STe (21.66 ± 1.77 ml·kg·min(-1)) (p = 0.035), but this difference was only seen for the first 20 minutes of exercise. Absolute VO2 values between sessions did not reveal differences. There were more statistically greater values in Ee compared to STe, regarding VO2 of lower limbs (25.44 ± 3.84 ml·kg·min(-1) versus 21.83 ± 2·24 ml·kg·min(-1); p = 0.038) and upper limbs (24.49 ± 3.84 ml·kg·min(-1) versus 21.54 ± 1.77 ml·kg·min(-1); p = 0.047). There were further significant differences regarding the moment effect (p<0.0001) of both STe and Ee sessions. With respect to the moment × session effect, only VO2 5 minutes into recovery showed significant differences (p = 0.017). In conclusion, although significant increases in VO2 were seen following Ee compared to STe, it appears that the load/intensity, and not the material/equipment used for the execution of an exercise, are variables that best influence oxygen uptake.